Design elements for gender-responsive breeding: The breeding cycle - Grando, Stefania (CGIAR Gender and Breeding Initiative, 2017)
Presented by Stefania Grando on 21 September 2017, as part of the webinar 'Design elements for gender-responsive breeding'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and the CGIAR Research Program on Roots, Tubers and Bananas.